365. Characteristics and outcomes of COVID-19 patients admitted to a regional health system in the southeast. (31st December 2020) - Teixeira, Charles; Shiflett, Henry; Jandhyala, Deeksha; Lewis, Jessica; Curry, Scott R; Salgado, Cassandra
Abstract: Background: COVID-19, first described in Wuhan, China, is now a global pandemic. We describe a cohort of patients (pts) admitted to our academic health system (HS) in the southeast, where demographics and comorbidities differ significantly from other regions in the U.S. Methods: This was a retrospective review of 161 consecutive pts admitted with COVID-19 from 3/12/20 to 6/1/20. We assessed demographics, comorbidities, presenting symptoms, treatments and outcomes and compared pts who died during hospitalization to those who survived to discharge (EpiInfo 7.2, Atlanta, GA). Results: Mean age was 60.5 years, 51.6% were female, 72% African American (AA) and 69.6% admitted from home. 54.5% had a BMI >30, 72% had HTN, 47.2% diabetes, and 33.6% COPD or asthma. The majority (68.8%) presented with fever (>38.0) and required supplemental oxygen within 8 hours of admission (63.4%). Cough (65.6%), dyspnea (57.5%), myalgias (30.6%) and diarrhea (23.8%) were also common. 40.4% received hydroxychloroquine, 23.6% steroids and 19.9% convalescent plasma. 42.9% required ICU care, 27.3% were intubated, and 19.3% died. Characteristics associated with death included older age, male sex, HTN, ESRD on HD, and cancer. Symptoms associated with death included absence of cough, absence of myalgias, previous admission for COVID-19, tachypnea, need for supplemental oxygen, elevated BUN and creatinine, and elevated ferritin. Interventions associated with death included use of steroids, receipt of ICU care, intubation, delay to intubation, and use of vasopressors or inotropes. Complications associated with death included development of a new arrhythmia, bacteremia, pneumonia, ARDS, thrombosis, and new renal failure requiring HD (Table). Table 1. Patient Characteristics by Death Table 2. Patient Characteristics by Death Table 3. Patient Characteristics by Death Conclusion: COVID-19 pts admitted to our southeast U.S. HS had significant comorbidities, most commonly obesity, HTN, and diabetes. Additionally, AA comprised a disproportionate share (72%) of our cohort compared to the general population of our state (30%), those tested in our region (32.9%), and those found to be positive for COVID-19 (35.8%). In-hospital mortality was 19.3% and intubation, particularly if delayed, was associated with death as were several complications, most notably arrhythmia, ARDS, and renal failure with HD. Disclosures: All Authors : No reported disclosures